2009
DOI: 10.1097/ypg.0b013e3283088e54
|View full text |Cite
|
Sign up to set email alerts
|

Positive association of neuroligin-4 gene with nonspecific mental retardation in the Qinba Mountains Region of China

Abstract: The results suggest a positive association between the genetic variants of the NLGN4 and NSMR in the Chinese children from Qinba Mountains Region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Nonetheless, our results are partially in agreement with Qi and collaborators (2009) that reported a positive association between SNPs in NLGN4X (rs6638575, rs3810686, rs1882260) and NSMR in a Chinese population [36]. In this regard, four putative haplotype combinations (rs3810686(T), rs1882260(T)), (rs3810686(C), −rs1882260(C)) and (rs6638575(G), rs3810686(T), rs18882260(T)) and (rs6638575(A), rs3810686(C), rs18882260(C)), in the sixth exon of NLGN4X have been reported as positively associated to NSMR in this Chinese cohort [36].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Nonetheless, our results are partially in agreement with Qi and collaborators (2009) that reported a positive association between SNPs in NLGN4X (rs6638575, rs3810686, rs1882260) and NSMR in a Chinese population [36]. In this regard, four putative haplotype combinations (rs3810686(T), rs1882260(T)), (rs3810686(C), −rs1882260(C)) and (rs6638575(G), rs3810686(T), rs18882260(T)) and (rs6638575(A), rs3810686(C), rs18882260(C)), in the sixth exon of NLGN4X have been reported as positively associated to NSMR in this Chinese cohort [36].…”
Section: Discussionsupporting
confidence: 93%
“…Deletion of exons 4, 5, and 6 in NLGN4X have been also found in autistic children, suggesting that alternative splicing variants might lead to abnormal neuroligin function in ASD [29,30]. Moreover, several noncoding genetic variants have been specifically found in ASD patients [31,32,33,34,35,36,37]. All these variations often segregate into ASD families [12,13] and can also be associated with different cognitive phenotypes, such as intellectual and language disabilities [32,37], highlighting the role of neuroligins in the ASD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have identified mutations in the genes encoding NLGN4 as a cause of autism spectrum disorders, Tourette's syndrome, learning disability and/ or schizophrenia [10][11][12][13][14][15] . A positive association between the genetic variants of NLGN4 and nonspecific mental retardation children of the Qinba region in China was also demonstrated in our previous study [16] . The description of the various mutations in NLGN4 seems to provide overwhelming evidence for a role of this gene in cognitive diseases.…”
Section: Introductionmentioning
confidence: 86%